The institutionalisation of experience capitalisation in MIVARF - Tarimo, Gilbert (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Marketing Infrastructure Value Addition and Rural Finance (MIVARF) support programme in Tanzania has gradually adopted the experience capitalisation approach and, in the process, has learnt six key lessons about its institutionalization.